Agriverde an agricultural technology development and innovation hub - Axalan, Agnes Andrea Z. (College of Architecture, University of the Philippines Diliman, 2019)
With the growing need to boost our agriculture industry through advancements in technology, the study aims to establish the need for a development that becomes a venue to showcase and develop agricultural technologies and induce an innovation ecosystem among the different key industry players in agriculture. The study proposes a development where farmers can learn about the agricultural technologies being developed in a setting where they are comfortable with. Entrepreneurs can improve and test the market with the products that they develop, and researchers can showcase advanced technologies being developed in various agricultural research institutions in the country. Lastly, it serves as a place where the government can utilize the development to support the farmers and researchers who make use of the facility through training programs and funding. The project aims to establish the relevance of an agricultural technology development and innovation hub that could help induce growth and collaboration among the different sectors in order to create a stronger more inclusive agriculture industry.